Edukasi Webinar Konseling Pendekatan Pikiran dan Perilaku sebagai Upaya Pencegahan Bullying di Lingkungan Sekolah Wahdah Islamiyah - M. Amirullah; Iskandar Iskandar; Muhammad Ammar Naufal; Fitriana Fitriana; Azwar Azwar (WAHATUL MUJTAMA': Jurnal Pengabdian Masyarakat, 2023)
Bullying is currently a phenomenon in the school environment and has been designated as one of the "grave transgressions" in Education by the Indonesian Minister of Education and Culture. Consequently, this phenomenon requires attention and concerted corrective-preventive efforts to minimize its occurrence within the school environment. The purpose of this community service activity is to foster comprehension and enhance the capabilities of teachers within the internal Wahdah Islamiyah, enabling them to prevent and address bullying through a thought and behavior approach. The counseling, employing a thought and behavior approach, essentially adopts a cognitive-behavioral approach that has been tailored for broader application among teachers within the internal Wahdah Islamiyah school system. The results of this community service initiative demonstrate an augmentation in the comprehension and proficiency of teachers at Internal Wahdah Islamiyah, empowering them to prevent and address bullying through a thought and behavior approach.